PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN KETERAMPILAN GERAK DASAR TARI ZAPIN KREASI PADA SISWA KELAS V SD NEGERI 138 PEKANBARU - Hesti Rahmadeni; Zariul Antosa; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine how the application method to create a basic motion demostrasi Zapin dance creations in class V students of SD Negeri 138 Pekanbaru. Problem Formulation in Research tidakan This class is "Does the application of the method of demonstration can improve basic motor skills Zapin dance at the fifth grade students of SD Negeri 138 Pekanbaru". The subject of this study is the fifth grade students of State Elementary School 138 Pekanbaru. Many students of class V are the subject of research is 32 students comprising 14 male students and 18 female students. Demonstration method of presenting the material is taught a lesson by the teacher to the students by demonstrating the model or the real thing, showing the order of procedure or process of making something of something happening to achieve the goal of teaching and learning outcomes achieved. The method used in this research is classroom action research is a classroom action research which comprises two cycles. To solve the problem of teachers in their professional development were studied on the activities of teachers, student activities are based on the category of highly skilled, skilled, fairly skilled and less skilled. Based on data analysis in this study can be concluded that the ability of students increased from the first cycle to the second cycle. This was evident at an early test of the 32 students who took the tests, students are categorized as skilled as many as 14 students and 18 students categorized fairly skilled. In tests the skills I increased to 28 students who are categorized skilled and 4 students were categorized fairly skilled. And the test of skills II increased to 32 students categorized as skilled. The average teacher activity in the first cycle is 65% with a skilled categories and increased in the second cycle to 91% by the highly skilled category. While the average student activity cycle I is 60% with a reasonably skilled categories and increased in the second cycle becomes 82.5% with highly skilled categories. It can be concluded that the use of methods of demonstration can improve the skills of basic motion steps Zapin dance creations fifth grade students of SDN 138 Pekanbaru.Keywords: basic motion dance, skill, method demonstrations, dance zapin